2014
DOI: 10.1002/emmm.201303016
|View full text |Cite
|
Sign up to set email alerts
|

Embelin inhibits endothelial mitochondrial respiration and impairs neoangiogenesis during tumor growth and wound healing

Abstract: In the normal quiescent vasculature, only 0.01% of endothelial cells (ECs) are proliferating. However, this proportion increases dramatically following the angiogenic switch during tumor growth or wound healing. Recent evidence suggests that this angiogenic switch is accompanied by a metabolic switch. Here, we show that proliferating ECs increasingly depend on mitochondrial oxidative phosphorylation (OxPhos) for their increased energy demand. Under growth conditions, ECs consume three times more oxygen than qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 52 publications
5
59
0
Order By: Relevance
“…For analysis of mitochondrial membrane potential, HeLa cells were stained with 10 μM JC‐1 (Invitrogen) for 30 min at 37°C and analyzed by flow cytometry. For the analysis by confocal microscopy, HeLa cells were seeded on cover slips and stained with 25 nM MitoTracker ® Red CMXRos (Invitrogen) in culture media at 37°C for 30 min (Coutelle et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of mitochondrial membrane potential, HeLa cells were stained with 10 μM JC‐1 (Invitrogen) for 30 min at 37°C and analyzed by flow cytometry. For the analysis by confocal microscopy, HeLa cells were seeded on cover slips and stained with 25 nM MitoTracker ® Red CMXRos (Invitrogen) in culture media at 37°C for 30 min (Coutelle et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Expanding on these findings, we first showed that the IAP antagonist Comp A inhibited tumor growth in immune‐competent mice bearing B16 melanoma tumors. In these studies, matrigel containing Comp A or vehicle was mixed with B16 cells and subcutaneously injected into the flank region of C57/Bl6 mice . In this syngeneic mouse melanoma model, tumor growth was significantly attenuated in the presence of Comp A compared to vehicle‐treated controls (Figs A and EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, repetition of cold stimulation over > 1 d was also necessary to elicit CREB1 activation and In a wound healing experiment, it was found that mitochondrial dysfunction induced by embelin hindered tissue repair [29]. CREB enhanced tissue repair by inducing the secretion of WNT1-inducible signaling protein 1 (WISP-1) [30].…”
Section: Discussionmentioning
confidence: 99%